Preparation method and application of photoelectric dual-output photonic crystal ionic gel

By incorporating photonic crystals into the ion gel, a photoelectric dual output photonic crystal ion gel is prepared, which solves the complexity of read response behavior of existing wearable devices when detecting human movement, and realizes the photoelectric dual response of mechanical discoloration and electrical signal changes, which is suitable for intelligent wearable sensors.

CN119875040AActive Publication Date: 2025-04-25YANGZHOU UNIV

Patent Information

Application Number
CN202510055727.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

When detecting human movements, existing wearable devices require complex instruments to read out the response behaviors, and the equipment flexibility and sensitivity requirements are high, making it difficult to obtain the response signals of intuitive visual colors in a convenient way.

Method used

By incorporating photonic crystals into the ionic gel, a photoelectric dual output photonic crystal ion gel is prepared. This gel fixes the photonic crystals in an ionic gel with good conductivity under the action of a magnetic field, achieving photoelectric dual responses of mechanical discoloration and electrical signal changes.

Benefits of technology

It realizes that visual response and electrical signal changes occur simultaneously under mechanical strain stimulation during human movement, with good toughness, frost resistance and adhesion, and is suitable for the field of intelligent wearable sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875040A_ABST
    Figure CN119875040A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of photoelectric dual-output photonic crystal ionic gels, which comprises the following steps: synthesizing Fe3O4 (at) PSSMA (at) SiO2 nanoparticles by a hydrothermal method, mixing the Fe3O4 (at) PSSMA (at) SiO2 nanoparticles in water, adding a monomer, an ionic liquid, a cross-linking agent and an initiator, and dissolving to obtain a gel precursor solution; the gel precursor solution is transferred into a mold, and the mold is placed in a magnetic field environment and heated; under the action of a magnetic field, the magnetic nanoparticles develop color in the ionic gel precursor solution, and the gel precursor solution is subjected to heating curing cross-linking reaction at the same time, so that the photonic crystal ionic gel is prepared. The photonic crystal is fixed in the ionic gel with good conductivity in a one-dimensional chain form under the action of a magnetic field, and through thermal initiation polymerization, the prepared ionic gel shows a structure color which is bright in color and is not influenced by an angle, has photoelectric double response of mechanical discoloration and electric signal change, and can be applied to the field of photoelectric detection. The concrete has good stretchability, toughness, freezing resistance and adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of an ion gel, and in particular to a preparation method and application of a photoelectric dual-output photonic crystal ion gel. Background Art

[0002] Ion gels are composed of ionic liquids and supporting networks, and have many excellent properties, including high sensitivity, high mechanical strength, good adhesion, and ultra-high ionic conductivity. These properties make ion gels widely used in many emerging fields such as flexible sensors, ionic skins, and wearable electronic devices. Due to the high flexibility and sensitivity requirements of wearable devices, complex instruments are usually required to read out the response behavior of wearable devices. These instruments are usually expensive and inconvenient to carry. Therefore, it is a new strategy to obtain the intuitive visual color response signal of wearable devices through the convenient way of touch.

[0003] In nature, visual signals are information carriers for biological communication. For example, peacocks use colorful tail feathers to attract the opposite sex. The bright colors on peacock feathers are called structural colors, which are very stable and durable. Due to the existence of photonic crystal structures inside organisms, specific colors are produced. Colloidal photonic crystals are periodic structures formed by the arrangement of micron-sized colloidal particles. They have characteristics such as photonic bandgap effect and structural color. When the periodic structure changes due to external stimuli, the structural color will also change accordingly, producing a visual response to mechanical strain stimulation. Therefore, mechanochromic photonic crystal ion gel can be prepared by integrating photonic crystals into ion gels. Combining the structural color of elastomers with ionic conductivity can be used as a flexible strain sensor, which can display light and electrical output at the same time. It also has great potential in the field of ion skin.

[0004] At present, in addition to mechanochromic hydrogels, there are also reports on electrochromic, photochromic and thermochromic hydrogel materials. For example, electrochromic ion gels with excellent physicochemical stability, high color contrast, fast response time and good durability over thousands of switching cycles (W.Poh, A.Eh, W.Wu, et al., Rapidly Photocurable Solid-State Poly (ionic liquid) Ionogels For Thermally Robust and Flexible Electrochromic Devices, 34 (2022) 2206952.), photochromic nanocomposite organic hydrogels with excellent mechanical properties, low temperature resistance, photochromic properties and UV blocking properties (J.Chen, T.Sun, et al., Tough, Transparent, and Anti-Freezing Nanocomposite Organohydrogels with Photochromic Properties, 13 (2021) 31180), thermochromic hydrogels whose colors can be switched between two modes at a specific temperature and have fast response and good mechanical properties (T.Wu, T.Yin, X.Hu, et al., A Thermochromic Hydrogel for Camouflage and Soft Display,8(2020)2000031)etc. Summary of the invention

[0005] Purpose of the invention: The purpose of the present invention is to provide a method for preparing an optoelectronic dual-output photonic crystal ion gel which not only has the structural color of the photonic crystal that is independent of angle, but also has the optoelectronic dual response of mechanical chromism and electrical signal change;

[0006] The second object of the present invention is to provide an application of the optoelectronic dual-output photonic crystal ion gel obtained by the above method in a wearable sensor for detecting human body motion.

[0007] Technical solution: The method for preparing the optoelectronic dual-output photonic crystal ion gel of the present invention comprises the following steps:

[0008] (1) Synthesis of Fe3O4@PSSMA@SiO2 nanoparticles by hydrothermal method;

[0009] (2) mixing Fe3O4@PSSMA@SiO2 nanoparticles in water, adding monomers, ionic liquids, crosslinking agents, and initiators, and obtaining a gel precursor solution after fully dissolving;

[0010] (3) The obtained gel precursor solution is transferred to a mold, the mold is placed in a magnetic field environment, and the mold is heated; under the action of the magnetic field, the magnetic nanoparticles are colored in the ion gel precursor solution, and the gel precursor solution is simultaneously heated and cured by a cross-linking reaction, thereby obtaining a photoelectric dual-output photonic crystal ion gel.

[0011] The specific process of step (1) is as follows: dissolving iron salt in ethylene glycol, adding sodium acetate, and sequentially adding poly(4-styrenesulfonic acid-co-maleic acid) sodium salt, L-ascorbic acid and deionized water while stirring, and then adding sodium hydroxide to carry out a solvothermal reaction; after the reaction is completed, performing magnetic separation, washing the separated product, and then dispersing it in deionized water to obtain an aqueous solution of Fe3O4@PSSMA nanoparticles;

[0012] The Fe3O4@PSSMA nanoparticle aqueous solution is mixed with anhydrous ethanol and ammonium hydroxide, stirred and heated, and tetraethyl silicate is added at intervals to react; after the reaction, the product is separated by a magnet to obtain Fe3O4@PSSMA@SiO2 colloid, and after washing, Fe3O4@PSSMA@SiO2 core-shell colloidal nanoparticles are obtained.

[0013] Wherein, in step (1), the mass ratio of ethylene glycol, iron salt, sodium acetate, poly(4-styrenesulfonic acid-co-maleic acid) sodium salt, L-ascorbic acid, deionized water and sodium hydroxide is 17.8:0.26:1.2:0.4:0.0045:0.02-0.05:0.24.

[0014] Wherein, in step (1), the mass ratio of Fe3O4@PSSMA nanoparticle aqueous solution, anhydrous ethanol and ammonium hydroxide is 3:15.8:0.86-0.96.

[0015] Wherein, in step (1), the amount of tetraethyl silicate added each time is 0.687-4.122:0.26, and the particle size of Fe3O4@PSSMA@SiO2 nanoparticles is regulated by controlling the amount of tetraethyl silicate added.

[0016] Wherein, in step (1), the solvent thermal reaction temperature is 190-200° C., and the heating time is 9-10 hours.

[0017] The specific process of step (2) is as follows: monomers acrylamide, N-vinyl pyrrolidone, carboxymethyl chitosan, crosslinking agent N,N'-methylenebisacrylamide, thermal initiator ammonium persulfate and Fe3O4@PSSMA@SiO2 colloidal nanoparticles are mixed and dissolved in a mixed solution of ionic liquid 1-ethyl-3-methylimidazole ethyl sulfate and deionized water, and a catalyst is added after dissolution to obtain a gel precursor solution by thermally initiated free radical polymerization.

[0018] Wherein, in step (2), the mass ratio of acrylamide, N-vinyl pyrrolidone, carboxymethyl chitosan, deionized water, N,N'-methylenebisacrylamide, ammonium persulfate and tetramethylethylenediamine is 21.3-36:18.7-33.4:25:60:0.1:0.08:0.4.

[0019] Wherein, in step (2), the mass ratio of acrylamide to Fe3O4@PSSMA@SiO2 is 3.1:0.01-0.02; the mass ratio of acrylamide to 1-ethyl-3-methylimidazole ethyl sulfate is 1:0-0.3.

[0020] The specific process of step (3) is as follows: pouring the gel precursor solution into a polytetrafluoroethylene mold, placing the polytetrafluoroethylene mold on or around the magnet, heating the mold and the precursor solution by a heat source to initiate a polymerization reaction, removing the heat source, and initiating the unreacted area by relying on the heat released by the polymerization reaction until the solution in the mold is completely converted into gel, and finally fixing the magnetic photonic crystal structure in the gel network to obtain a photonic crystal ion gel with optical and electrical dual output under strain stimulation.

[0021] Wherein, in step (3), the magnetic field strength of the magnet is 5000 to 8000 Gs.

[0022] Wherein, in step (3), heating is performed so that the thermal initiation temperature is 50 to 60°C.

[0023] The optoelectronic dual-output photonic crystal ion gel obtained by the above method is used in a wearable sensor for detecting human motion.

[0024] Principle of the invention: The present invention proposes a simple method for preparing photoelectric dual-output photonic crystal ion gel with multifunctional characteristics through rapid magnetic assembly and free radical polymerization, with acrylamide, N-vinyl pyrrolidone, carboxymethyl chitosan, ionic liquid 1-ethyl-3-methylimidazolium ethyl sulfate (EMIES for short), water, N,N'-methylenebisacrylamide, ammonium persulfate and tetramethylethylenediamine mixture as gel precursor solution, combined with magnetically assembled Fe3O4@PSSMA@SiO2 colloidal nanoparticles (CNs). Rapid magnetic induction assembly of Fe3O4@PSSMA@SiO2 colloidal nanoparticles (CNs) in the ion gel precursor solution embeds a one-dimensional CPC chain structure in the ion gel framework, and successfully prepares a solid cross-linked color ion gel with PBG characteristics. The photonic crystal ion gel prepared by this method has good toughness, excellent antifreeze and adhesion. Since the ion gel has a structural color that is independent of angle, it has a synchronous electrical response and visual response to mechanical strain stimulation during human movement. This fast self-assembled PC hydrogel can be used as a multi-signal device and has great potential in human motion recording applications in the field of smart wearable sensors.

[0025] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:

[0026] (1) The method of the present invention fixes the photonic crystal in the form of a one-dimensional chain in an ion gel with good electrical conductivity under the action of a magnetic field. Through thermally initiated polymerization, the prepared ion gel shows a bright color and structural color that is not affected by angles. It also has a photoelectric dual response of mechanical color change and electrical signal change, good stretchability, toughness, frost resistance, adhesion, and can work normally in a low-temperature environment. (2) The present invention cross-links and polymerizes NVP and AAM, which significantly improves the ductility and toughness of the gel. In addition, the addition of ionic liquid improves the conductivity, frost resistance and stretchability of the gel, and the introduction of chitosan gives the gel adhesion. (3) The method of the present invention is simple and has low energy consumption. Through magnetic assembly and thermally initiated polymerization, the preparation of photoelectric dual-output photonic crystal ion gel can be completed in one step in a short time; mechanical strain stimulation of the gel will cause its color to change, and the resistance will also change synchronously, with synchronous electrical response and visual response. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The stress-strain curve (a) and the elongation at break and Young's modulus diagram (b) of the photonic crystal ion gel material prepared in Examples 1-5 at room temperature;

[0028] Figure 2 Photonic crystal ion gel columns prepared in Example 6 and Example 7 and photos of the color changes when the pressure increases;

[0029] Figure 3 These are photos of the circular photonic crystal ion gel film prepared in Example 3 under mechanical bending and microtouch stimulation;

[0030] Figure 4 DSC measurement of the photonic crystal ion gel material prepared in Examples 1-5 (a) and torsion, stretching and bending images after freezing at -20°C overnight (b);

[0031] Figure 5 The graph of the change of the ion gel structural color and the change of the brightness of the LED bulb of the photoelectric dual-output photonic crystal ion gel prepared in Example 3 during the 50% strain stretching cycle;

[0032] Figure 6 The corresponding reflection spectrum of the optoelectronic dual-output photonic crystal ion gel prepared in Example 3 under 0% to 50% tensile strain;

[0033] Figure 7 This is a sensitivity diagram of the optoelectronic dual-output photonic crystal ion gel prepared in Example 3 under 0% to 250% strain;

[0034] Figure 8 This is a comparison diagram of the relative resistance change of the photonic crystal ion gel prepared in Example 3 at a large strain of 40% to 200%;

[0035] Fig. 9 This is a resistance change diagram of the photonic crystal ion gel prepared in Example 3 after repeated loading and unloading for 500 times under 50% tensile strain. DETAILED DESCRIPTION

[0036] The present invention is described in further detail below.

[0037] Example 1

[0038] (1) Dissolve 0.52g of ferric chloride (FeCl3) in 35.6g of ethylene glycol (EG), ultrasonicate for 5 minutes, add 2.4g of sodium acetate (CH3COONa) and stir magnetically, and add 0.8g of poly (4-styrenesulfonic acid-co-maleic acid) sodium salt (PSSMA), 0.009g of L-ascorbic acid (vitamin C, AA) and 0.6g of deionized water (H2O) in sequence while stirring, stir for 1 hour, add 0.48g of sodium hydroxide (NaOH) while stirring, and stir magnetically for 3 hours. Transfer to a reactor, heat to react, wait for the reactor to cool, separate by magnetization, wash five times with a 1:1 ethanol / water mixture and deionized water, and finally disperse in 25g of deionized water to obtain a Fe3O4@PSSMA nanoparticle aqueous solution;

[0039] (2) The aqueous solution of 6g Fe3O4@PSSMA nanoparticles prepared in (1) was mixed with 31.6g anhydrous ethanol (C2H5OH) and 1.82g ammonium hydroxide (NH4OH), and ultrasonicated for 5 minutes. The mixture was then transferred to a 250ml three-necked flask. After stirring at 520rpm in a 50℃ water bath for 10 minutes, 200ul tetraethyl silicate (TEOS) was slowly added every 20 minutes for 3 times. After stirring for 2h, the obtained Fe3O4@PSSMA@SiO2 colloid was separated by a magnet, and washed with ethanol and water 3 times to finally obtain Fe3O4@PSSMA@SiO2 core-shell colloidal nanoparticles;

[0040] (3) Preparation by thermally initiated free radical polymerization: First, 3.072 g acrylamide (AAM), 2.197 g N-vinyl pyrrolidone (NVP), 0.25 g chitosan (CMC), 0.01 g cross-linking agent N,N'-methylenebisacrylamide (MBAA), 0.008 g thermal initiator ammonium persulfate (APS) and 0.015 g Fe3O4@PSSMA@SiO2 colloidal nanoparticles prepared in step (2) were mixed and dissolved in 6 g solvent deionized water, and after ultrasonic dissolution, 0.04 g catalyst tetramethylethylenediamine (TEMED) was added and fully dissolved and mixed to obtain a gel precursor solution;

[0041] (4) Pour the obtained gel precursor solution into a polytetrafluoroethylene mold, place the mold on top of a 5000Gs magnet, and heat it at 50°C for 3 minutes to solidify it. The product prepared in this example is a photonic crystal ion gel AAM-NVP-EM0 with dual output of light and electricity.

[0042] Example 2

[0043] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (3), the mass of the solvent deionized water and the ionic liquid are 5.76 g and 0.24 g respectively, and the mass fraction of the ionic liquid is 2%. The product prepared in this embodiment is the photonic crystal ion gel AAM-NVP-EM2 with dual output of light and electricity.

[0044] Example 3

[0045] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (3), the mass of the solvent deionized water and the ionic liquid are 5.52 g and 0.48 g respectively, and the mass fraction of the ionic liquid is 4%. The product prepared in this embodiment is the photonic crystal ion gel AAM-NVP-EM4 with dual output of light and electricity.

[0046] Example 4

[0047] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (3), the mass of the solvent deionized water and the ionic liquid are 5.30 g and 0.7 g respectively, and the mass fraction of the ionic liquid is 6%. The product prepared in this embodiment is the photonic crystal ion gel AAM-NVP-EM6 with dual output of light and electricity.

[0048] Example 5

[0049] The preparation method of this embodiment is the same as that of embodiment 1, except that in step (3), the mass of the solvent deionized water and the ionic liquid are 5.06 g and 0.94 g respectively, and the mass fraction of the ionic liquid is 8%. The product prepared in this embodiment is the photonic crystal ion gel AAM-NVP-EM8 with dual output of light and electricity.

[0050] Example 6

[0051] The preparation method of this embodiment is the same as that of embodiment 3, except that the gel precursor solution obtained in step (3) is poured into a test tube, the test tube is placed on one side of a 5000GS magnet and perpendicular to the table, and heated at 50°C for 3 minutes to solidify. The product prepared in this embodiment is a green photoelectric dual-output photonic crystal ion gel column.

[0052] Example 7

[0053] The preparation method of this embodiment is the same as that of embodiment 6, except that in step (1), only 200ul of tetraethyl silicate (TEOS) is added. The product prepared in this embodiment is a purple photoelectric dual-output photonic crystal ion gel column.

[0054] Comparative Example 1

[0055] The preparation method of this comparative example is the same as that of Example 1, except that in step (3), the masses of the solvent deionized water and the ionic liquid are 4.82 g and 1.18 g, respectively, and at this time, the mass fraction of the ionic liquid is 10%. In step (3), the hydrogel precursor solution is not completely dissolved after 2 hours of ultrasound, and there is a small amount of polymerization in the hydrogel precursor solution. 0.04 g of catalyst tetramethylethylenediamine (TEMED) is added, and the obtained gel precursor solution is poured into a polytetrafluoroethylene mold and placed above a magnet, and heated at 50°C for 3 minutes to solidify it. The obtained ion gel is dark in color and uneven in color. This indicates that the excessive amount of ionic liquid leads to incomplete dissolution and affects the color development of the photonic crystal in the ion gel.

[0056] Characterization and performance testing of the products prepared in each example:

[0057] The ion gel was tensile tested at room temperature using a universal testing machine with a 1000N sensor (Instron 3367, USA). The crosshead tensile speed was 20 mm / min, the standard strip was 4 mm wide, 1.5 mm thick, and 30 mm long, and at least 5 parallel tests were performed.

[0058] Figure 1 The stress-strain curve (a) and the elongation at break and Young's modulus (b) of the photonic crystal ion gel material prepared in Examples 1-5 are shown in FIG. Figure 1 In (b), the column with number 1 represents the left vertical coordinate, and the column with number 2 represents the right vertical coordinate. Figure 1 As shown in (a) and (b), when the mass fraction of EMIES added to AAM-NVP-EM ion gel ranges from 0wt% to 8wt%, the elongation at break of the material increases from 1231% to 1790%, and the Young's modulus decreases from 31.4kPa to 14.2kPa. With the increase of EMIES content, the elongation at break of AAM-NVP-EM ion gel increases significantly. However, there is a trade-off between elongation at break and mechanical strength. When the EMIES content is 8%, the elongation at break of AAM-NVP-EM8 ion gel is the largest, but the mechanical strength is low. Therefore, EMIES content of 4wt% is selected as the optimal composition.

[0059] Figure 2 The green and purple photoelectric dual-output photonic crystal ion gel column prepared in Example 6 and Example 7, wherein: Figure 2 (a) is Example 6, and (b) is Example 7. Figure 2 It can be seen that as the pressure increases, the photonic crystal ion gel column exhibits an obvious red-shifted structural color. When the pressure increases, the color of the green ion gel column changes from green to dark red, and as the pressure is released, the color returns to the original green; correspondingly, the blue ion gel column changes from blue to orange, and returns to the original blue after the pressure is released. In Examples 1 to 5, the mold containing the gel precursor solution is placed horizontally on the top of a horizontally placed magnet and heated and polymerized to obtain a strip of photonic crystal ion gel, while in Examples 6 and 7, the test tube containing the gel precursor solution is placed on one side of the magnet and placed vertically on the table, heated and polymerized to obtain a columnar photonic crystal ion gel.

[0060] Figure 3The green circular photonic crystal ion gel film prepared in Example 3 was transferred to black cardboard. When the surface of the green circular film was compressed by bending, the central part of the film turned orange; and when the surface was bent and stretched, the entire surface turned lavender. At the local point where mechanical stimulation was applied, an instant color response could be shown, and a slight touch of the edge of the green circular film with tweezers would result in an obvious local color change.

[0061] Differential scanning calorimeter (DSC, 204F1, Netzsch Co., Germany) was used to evaluate the low temperature resistance of the photonic crystal ion gel with dual output of light and electricity. The scanning rate and temperature range were 2 °C min -1 and -65°C to 20°C. All tests were performed under N2 atmosphere.

[0062] Figure 4 is the DSC curve of the photonic crystal ion gel material prepared in Example 1-4. Figure 4 From the DSC curve of (a), it can be seen that when the EMIES content is 0%, there is a peak at -39°C, indicating that the hydrogel without EMIES molecules is frozen at around -39°C. When the EMIES content is 2wt%, 4wt% and 6wt%, the photonic crystal ion gel has no heat flow curve peak in the temperature range of -60°C to 20°C. This result shows that the ionic liquid EMIES molecules can form a large number of hydrogen bonds with water, affecting the crystallization of water and lowering the freezing point of the hydrogel. The addition of EMIES lowers the freezing point of water and improves the low temperature resistance of the photonic crystal ion gel. Figure 4 In (b), the photonic crystal ion gel was placed in a refrigerator at -25°C for 24 hours. It was found that the sample did not freeze and still had high elasticity. It could withstand various deformations such as torsion, stretching and bending without damage, indicating that it has excellent antifreeze behavior at sub-zero temperatures and its mechanical properties are not affected by the ambient temperature. At the same time, the structural color of the photonic crystal ion gel did not change when it was deformed, indicating that its structural color was not affected in a low temperature environment.

[0063] The electrical signal of the photonic crystal ion gel was measured using a digital bridge (TH2830). The strain and pressure sensing properties of the gel during stretching were evaluated by placing the sample on the digital bridge and performing a tensile test using a universal testing machine.

[0064] Figure 5 The photonic crystal ion gel prepared in Example 3 shows the change in the ion gel structural color and the change in the brightness of the LED bulb, as well as the stability of the sensitivity and electrical signal output when the photonic crystal ion gel, LED lamp and power supply are connected in series in the circuit. Figure 5It can be observed that the light bulb in the circuit lights up, indicating that the photonic crystal ion gel is conductive.

[0065] Figure 6 The change of the reflectance spectrum of the photonic crystal ion gel during the stretching process from 0% to 50% is shown. When the deformation of the photonic crystal ion gel increases, the color of the photonic crystal ion gel shifts to blue, and the brightness of the light bulb dims; then when the deformation decreases, the color of the photonic crystal ion gel shifts to red, and the light bulb becomes brighter again. This shows that mechanical strain stimulation of the optoelectronic dual-output photonic crystal ion gel will have synchronous electrical and visual responses.

[0066] Figure 7 The photonic crystal ion gel prepared in Example 3 is shown to gradually increase the resistance ratio of the ion gel as the strain increases from 0 to 250%, and the linearity reaches 0.982. During the stretching process, the hydrogel strips gradually elongate, resulting in an increase in the length and resistance of the conductive path. The sensitivity of the ion gel is a key consideration in the strain detection capability, which is quantified using the gauge factor (GF). The GF value of the conductive hydrogel reaches 0.837.

[0067] Figure 8 It can be observed that, in the photonic crystal ion gel prepared in Example 3, ΔR / R0 is relatively stable within the strain range of 40% to 200%, and ΔR / R0 increases with the increase of deformation, showing an arithmetic difference phenomenon.

[0068] Fig. 9 The photonic crystal ion gel prepared in Example 3 was subjected to a 500-cycle tensile test under a small strain of 50%. Except for a slight deviation in the baseline, the other data are comparable, and there is no significant difference in the amplitude and waveform within the range of 500 cycles, indicating that the photonic crystal ion gel has excellent stability. These characteristics confirm that the photoelectric dual-output photonic crystal ion gel prepared by the present invention has a high potential application value in the field of wearable sensors for monitoring human movement.

Claims

1. A method for preparing a photoelectric dual-output photonic crystal ion gel, characterized in that: The following steps are involved: (1) Synthesis of Fe3O4@PSSMA@SiO2 nanoparticles by hydrothermal method; (2) mixing Fe3O4@PSSMA@SiO2 nanoparticles in water, adding monomers, ionic liquids, crosslinking agents, and initiators, and obtaining a gel precursor solution after full dissolution; (3) The obtained gel precursor solution is transferred to a mold, the mold is placed in a magnetic field environment, and the mold is heated; under the action of the magnetic field, the magnetic nanoparticles are colored in the ion gel precursor solution, and the gel precursor solution is simultaneously heated and cured by a cross-linking reaction, thereby obtaining a photoelectric dual-output photonic crystal ion gel.

2. The method for preparing the optoelectronic dual-output photonic crystal ion gel according to claim 1, characterized in that: The specific process of step (1) is as follows: dissolving iron salt in ethylene glycol, adding sodium acetate, and sequentially adding poly(4-styrenesulfonic acid-co-maleic acid) sodium salt, L-ascorbic acid and deionized water while stirring, and then adding sodium hydroxide to carry out a solvothermal reaction; after the reaction is completed, performing magnetic separation, washing the separated product, and then dispersing it in deionized water to obtain an aqueous solution of Fe3O4@PSSMA nanoparticles; The Fe3O4@PSSMA nanoparticle aqueous solution is mixed with anhydrous ethanol and ammonium hydroxide, stirred and heated, and tetraethyl silicate is added at intervals to react; after the reaction, the product is separated by a magnet to obtain Fe3O4@PSSMA@SiO2 colloid, and after washing, Fe3O4@PSSMA@SiO2 core-shell colloidal nanoparticles are obtained.

3. The method for preparing the optoelectronic dual-output photonic crystal ion gel according to claim 1, characterized in that: The specific process of step (2) is: monomer acrylamide, N-vinyl pyrrolidone, carboxymethyl chitosan, crosslinking agent N,N'-methylenebisacrylamide, thermal initiator ammonium persulfate and Fe3O4@PSSMA@SiO2 colloidal nanoparticles are mixed and dissolved in a mixed solution of ionic liquid 1-ethyl-3-methylimidazole ethyl sulfate and deionized water, and a catalyst is added after dissolution to obtain a gel precursor solution through a thermally initiated free radical polymerization method.

4. The method for preparing the optoelectronic dual-output photonic crystal ion gel according to claim 1, characterized in that: The specific process of step (3) is as follows: pouring the gel precursor solution into a polytetrafluoroethylene mold, placing the polytetrafluoroethylene mold on or around the magnet, heating the mold and the precursor solution by a heat source to initiate a polymerization reaction, removing the heat source, and initiating the unreacted area by relying on the heat released by the polymerization reaction until the solution in the mold is completely converted into gel, and finally fixing the magnetic photonic crystal structure in the gel network to obtain a photonic crystal ion gel with optical and electrical dual output under strain stimulation.

5. The method for preparing the optoelectronic dual-output photonic crystal ion gel according to claim 1, characterized in that: In step (3), the magnetic field strength is 5000 to 8000 Gs.

6. The method for preparing the optoelectronic dual-output photonic crystal ion gel according to claim 1, characterized in that: In step (3), heating is performed so that the thermal initiation temperature is 50 to 60°C.

7. The method for preparing the optoelectronic dual-output photonic crystal ion gel according to claim 2, characterized in that: In step (1), the mass ratio of ethylene glycol, iron salt, sodium acetate, poly (4-styrenesulfonic acid-co-maleic acid) sodium salt, L-ascorbic acid, deionized water and sodium hydroxide is 17.8:0.26:1.2:0.4:0.0045:0.02-0.05:0.24; the mass ratio of the Fe3O4@PSSMA nanoparticle aqueous solution, anhydrous ethanol and ammonium hydroxide is 3:15.8:0.86-0.96; the mass ratio of tetraethyl silicate to iron salt added each time is 0.687-4.122:0.26, and the particle size of Fe3O4@PSSMA@SiO2 nanoparticles is regulated by controlling the amount of tetraethyl silicate added.

8. The method for preparing the optoelectronic dual-output photonic crystal ion gel according to claim 2, characterized in that: In step (1), the solvent thermal reaction temperature is 190-200° C., and the heating time is 9-10 hours.

9. The method for preparing the optoelectronic dual-output photonic crystal ion gel according to claim 3, characterized in that: In step (2), the mass ratio of acrylamide, N-vinyl pyrrolidone, carboxymethyl chitosan, deionized water, N,N'-methylenebisacrylamide, ammonium persulfate, and tetramethylethylenediamine is 21.3-36:18.7-33.4:25:60:0.1:0.08:0.4; the mass ratio of acrylamide and Fe3O4@PSSMA@SiO2 is 3.1:0.01-0.02; the mass ratio of acrylamide and 1-ethyl-3-methylimidazole ethyl sulfate is 1:0-0.

3.

10. Use of the optoelectronic dual-output photonic crystal ion gel obtained by the method according to claim 1 in a wearable sensor for detecting human motion.

Citation Information

Patent Citations

  • Preparation method of ionic liquid composite magnetic imprinted microspheres

    CN103130956A

  • Magnetic responsive photonic crystal, and simple large-scale preparation method and application thereof

    CN110787743A

  • Preparation method and application of Fe3O4-coated SiO2 photonic crystal organogel

    CN116693748A

  • Photoelectric dual-mode responsive photonic crystal hydrogel suitable for DLP three-dimensional forming

    CN119039622A

  • Preparation and Application of Magnetic Metallic Oxide Cross-Linked Acidic Polyionic Liquid

    US20190217281A1

Cited By

  • Self-adaptive dual-mode photoelectric gel interface material and preparation method and application thereof

    CN121086127A